New first-line immunotherapy-based combinations for metastatic renal cell carcinoma: A systematic review and network meta-analysis. (May 2022) - Lombardi, Pasquale; Filetti, Marco; Falcone, Rosa; Di Bidino, Rossella; Iacovelli, Roberto; Ciccarese, Chiara; Bria, Emilio; Tortora, Giampaolo; Scambia, Giovanni; Daniele, Gennaro
Highlights: Head-to-head comparisons do not exist for the newest treatments of metastatic renal cell carcinoma. In our network meta-analysis, lenvatinib plus pembrolizumab has the highest probability to be the best choice. This analysis could be used to help physicians while awaiting formal comparisons. Nevertheless, our results do not aim to produce formal recommendations. Prospective comparison trials are needed. Abstract: Several first-line immune-checkpoints inhibitors (ICI) based combinations have been studied in metastatic renal cell carcinoma (mRCC) without any direct comparison between the regimens. The objective of this systematic review and network meta-analysis was to provide the most updated evidence about the preferred first line ICI-based regimen for mRCC. We searched various databases, including PubMed, Web of Science and Scopus and the major conference proceedings (ASCO, ESMO). Eligible studies were randomized trial, published before June 2021 that evaluated first-line, ICI-based combinations compared with the standard of care in mRCC. Screening was performed independently by two investigators. A Cochrane risk-of-bias tool was used to assess trial quality. Relative effects of competing treatments were assessed by Bayesian network meta-analysis. The Preferred Reporting Items for Systematic Reviews and Meta-analyses guideline was used. Outcomes included overall survival (OS), progression-free survival (PFS), overall response rate, complete response and adverse events. Six trials with 5478 patients comparing 7 treatments were identified. Network meta-analysis showed that lenvatinib plus pembrolizumab had the highest probability to be the best treatment in terms of OS (surface under the cumulative ranking (SUCRA) 80.7%) and PFS (SUCRA 99.6%), while in sarcomatoid patients, nivolumab plus cabozantinib had the highest rank in terms of survival outcomes (SUCRA 85.8% and SUCRA 77.3%, respectively). Although we established a ranking among new first-line mRCC treatment combinations, the absence of direct comparisons between the multiple treatment options represents a major hurdle in establishing optimal therapeutic sequences. Our results could represent a starting point for head-to-head trials between the most promising combinations.